The Scientific Structure of Good Governance and Digital Government Transformation: A Bibliometric Analysis - Arwan. H; Juanda Nawawi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the scientific structure of research on good governance and digital government transformation using a bibliometric approach. The increasing integration of digital technologies in public administration has generated significant academic interest, necessitating a systematic mapping of the field. This study employs data retrieved from the Scopus database, covering 428 documents published between 1992 and 2026. The analysis is conducted using the Bibliometrix package in R, incorporating performance analysis and science mapping techniques, including co-authorship networks, country collaboration, thematic evolution, and keyword co-occurrence. The results indicate a steady growth of research with an annual growth rate of 8.07%, reflecting the rising importance of digital transformation in governance. The field is characterized by a decentralized structure, with contributions distributed across multiple journals, institutions, and countries. Leading contributors include the United Kingdom, China, South Africa, and the United States, while collaboration patterns show a dominance of single-country publications. Thematic analysis reveals a shift from foundational governance concepts toward sustainability, digital transformation, and sector-specific applications such as energy policy and smart cities. This study contributes to the literature by providing a comprehensive overview of the intellectual, social, and conceptual structure of the field. The findings offer valuable insights for researchers and policymakers in understanding emerging trends and guiding future research directions in digital governance.